Two Distinct Assembly States of the Cysteine Regulatory Complex of Salmonella typhimurium Are Regulated by Enzyme–Substrate Cognate Pairs - Kaushik, Abhishek; Ekka, Mary Krishna; Kumaran, Sangaralingam (Biochemistry (Easton), 2017)
Serine acetyltransferase (SAT) and O-acetylserine sulfhydrylase (OASS), which catalyze the last two steps of cysteine biosynthesis, interact and form the cysteine regulatory complex (CRC). The current model of Salmonella typhimurium predicts that CRC is composed of one [SAT]hexamer unit and two molecules of [OASS]dimer. However, it is not clear why [SAT]hexamer cannot engage all of its six high-affinity binding sites. We examined the assembly state(s) of CRC by size exclusion chromatography, analytical ultracentrifugation (AUC), isothermal titration calorimetry (ITC), and surface plasmon resonance (SPR) approaches. We show that CRC exists in two major assembly states, low-molecular weight (CRC1; 1[SAT]hexamer + 2[OASS]dimer) and high-molecular weight (CRC2; 1[SAT]hexamer + 4[OASS]dimer) states. Along with AUC results, ITC and SPR studies show that [OASS]dimer binds to [SAT]hexamer in a stepwise manner but the formation of fully saturated CRC3 (1[SAT]hexamer + 6[OASS]dimer) is not favorable. The fraction of CRC2 increases as the [OASS]dimer/[SAT]hexamer ratio increases to >4-fold, but CRC2 can be selectively dissociated into either CRC1 or free enzymes, in the presence of OAS and sulfide, in a concentration-dependent manner. Together, we show that CRC is a regulatable multienzyme assembly, sensitive to OASS–substrate(s) levels but subject to negative cooperativity and steric hindrance. Our results constitute the first report of the dual-assembly-state nature of CRC and suggest that physiological conditions, which limit sulfate uptake, would favor CRC1 over CRC2.